Clinical Characteristics of COVID-19 Patients in a Regional Population With Diabetes Mellitus: The ACCREDIT Study - Llanera, Daniel Kevin; Wilmington, Rebekah; Shoo, Haika; Lisboa, Paulo; Jarman, Ian; Wong, Stephanie; Nizza, Jael; Sharma, Dushyant; Kalathil, Dhanya; Rajeev, Surya; Williams, Scott; Yadav, Rahul; et al. (Frontiers in Endocrinology, 2022)
Objective To identify clinical and biochemical characteristics associated with 7- & 30-day mortality and intensive care admission amongst diabetes patients admitted with COVID-19. Research Design and Methods We conducted a cohort study collecting data from medical notes of hospitalised people with diabetes and COVID-19 in 7 hospitals within the Mersey-Cheshire region from 1 January to 30 June 2020. We also explored the impact on inpatient diabetes team resources. Univariate and multivariate logistic regression analyses were performed and optimised by splitting the dataset into a training, test, and validation sets, developing a robust predictive model for the primary outcome. Results We analysed data from 1004 diabetes patients (mean age 74.1 (± 12.6) years, predominantly men 60.7%). 45% belonged to the most deprived population quintile in the UK. Median BMI was 27.6 (IQR 23.9-32.4) kg/m2. The primary outcome (7-day mortality) occurred in 24%, increasing to 33% by day 30. Approximately one in ten patients required insulin infusion (9.8%). In univariate analyses, patients with type 2 diabetes had a higher risk of 7-day mortality (p < 0.05, OR 2.52 [1.06, 5.98]). Patients requiring insulin infusion had a lower risk of death (p = 0.02, OR 0.5 [0.28, 0.9]). CKD in younger patients (<70 years) had a greater risk of death (OR 2.74 [1.31-5.76]). BMI, microvascular and macrovascular complications, HbA1c, and random non-fasting blood glucose on admission were not associated with mortality. On multivariate analysis, CRP and age remained associated with the primary outcome (OR 3.44 [2.17, 5.44]) allowing for a validated predictive model for death by day 7. Conclusions Higher CRP and advanced age were associated with and predictive of death by day 7. However, BMI, presence of diabetes complications, and glycaemic control were not. A high proportion of these patients required insulin infusion warranting increased input from the inpatient diabetes teams.